An Adapted Group Method of Data Handling for Abrupt Data Analysis (International Journal of Engineering and Computer Science, 2014)
This Research paper shows the experimental study for the Agricultural (Economical) yield prediction output those are based on the past data using Group Method of Data Handling (GMDH) technique. GMDH is very useful concept for solving the real life problem. Because in real life the data is vast, it is dynamic in behavior and complex in nature. The usability of Group Method of Data Handling is to select the useful input from all data set and discard the useless data using external criterion. Useless data not only reduce the performance of the system but also give the inaccurate result.